Rac-1 promotes pulmonary artery smooth muscle cell proliferation by upregulation of plasminogen activator inhibitor-1: Role of NFκB-dependent hypoxia-inducible factor-1α transcription - Diebold, Isabel; Djordjevic, Talija; Hess, John; Görlach, Agnes (Thrombosis and Haemostasis, 2008)
Pulmonary vascular remodeling is commonly associated with pulmonary hypertension and is characterized by media thickening and disordered cellular proliferation, often accompanied by fibrin deposition and thrombosis in situ. However, the signaling pathways linking these different processes are not well understood. Since the GTPase Rac-1 has been suggested to act as a signaling relay in various cell types we investigated whether Rac-1 could be the link between thrombin signaling,plasminogen activator inhibitor-1 (PAI-1), which inhibits fibrinolysis and promotes fibrin deposition, and proliferation of pulmonary artery smooth muscle cells (PASMC). Exposure to thrombin enhanced the levels of Rac-1 protein and increased PAI-1 mRNA and protein expression in dependence of the thrombin receptor PAR-1. Expression of dominant-negative Rac-1 (RacT17N) prevented thrombin-induced PAI-1 expression whereas constitutively active RacG12V enhanced PAI-1 levels. In the presence of RacT17N thrombin-induced PAI-1 promoter activity was abrogated whereas RacG12V increased PAI-1 promoter activity, and this response was essentially dependent on the transcription factor hypoxia-inducible factor-1 (HIF-1). Subsequently, RacG12V not only increased HIF transcriptional activity but also HIF-1α protein and mRNA levels, whereas RacT17N prevented these responses elicited by thrombin.In line,RacG12V enhanced HIF-1α promoter activity, and this response was dependent on nuclear factor-kappaB (NFκB) binding to the HIF-1α promoter. Finally, upregulation of PAI-1 by Rac-1 and HIF-1 was essential for thrombin-stimulated proliferation of PASMC.These findings indicate that Rac-1 is an important mediator of thrombin signaling and may contribute to pulmonary vascular remodeling via HIF-1-dependent upregulation of PAI-1 leading to enhanced proliferation of PASMC.
Keywords: Thrombin; PAR-1; plasminogen activator inhibitor-1; Rac-1; hypoxia-inducible factor-1; pulmonary vascular remodeling; smooth muscle cells